2013
DOI: 10.1186/1471-2407-13-24
|View full text |Cite
|
Sign up to set email alerts
|

Specific genes involved in synthesis and editing of heparan sulfate proteoglycans show altered expression patterns in breast cancer

Abstract: BackgroundThe expression of a specific set of genes controls the different structures of heparan sulfate proteoglycans (HSPGs), which are involved in the growth, invasion and metastatic properties of cancerous cells. The purpose of this study is to increase knowledge of HSPG alterations in breast cancer.MethodsTwenty-three infiltrating ductal adenocarcinomas (IDCs), both metastatic and non-metastatic were studied. A transcriptomic approach to the structure of heparan sulfate (HS) chains was used, employing qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 41 publications
2
63
0
Order By: Relevance
“…According Affimetrix microarray analysis, only 9 of 100 GAG biosynthesis-involved genes (EXT2, CHSY3, CSGALNACT1, HS3ST2, HS2ST1, CHST11, CSGALNACT2, HPSE, SULF2) are significantly different between normal and malignant human plasma cells, while the rest genes remain unchanged; 30 6 of 15 GAG biosynthesis-involved genes are changed in neuroendocrine tumors; 31 7 of 21 key HS-synthesising genes are significantly deregulated in breast cancer. 32 Although the obtained results were not analyzed in terms of overall configuration of GAG-biosynthetic machinery in tumors, they support a common disbalance of the system in cancer. Complex analysis of transcriptional activity of HS biosynthetic system in normal prostate tissue and tumors showed significant downregulation of total transcriptional activity of HS biosynthetic system and changes in overall expression patterns in prostate cancer, 33 whereas in colon cancer only qualitative changes in expression patterns are detected.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…According Affimetrix microarray analysis, only 9 of 100 GAG biosynthesis-involved genes (EXT2, CHSY3, CSGALNACT1, HS3ST2, HS2ST1, CHST11, CSGALNACT2, HPSE, SULF2) are significantly different between normal and malignant human plasma cells, while the rest genes remain unchanged; 30 6 of 15 GAG biosynthesis-involved genes are changed in neuroendocrine tumors; 31 7 of 21 key HS-synthesising genes are significantly deregulated in breast cancer. 32 Although the obtained results were not analyzed in terms of overall configuration of GAG-biosynthetic machinery in tumors, they support a common disbalance of the system in cancer. Complex analysis of transcriptional activity of HS biosynthetic system in normal prostate tissue and tumors showed significant downregulation of total transcriptional activity of HS biosynthetic system and changes in overall expression patterns in prostate cancer, 33 whereas in colon cancer only qualitative changes in expression patterns are detected.…”
Section: Introductionmentioning
confidence: 81%
“…[35][36][37] Earlier, a similar idea was applied in few studies, where expression of a number of GAG biosynthesis-involved genes in different normal and cancer tissues were investigated simultaneously, [30][31][32] however the obtained results were not analyzed in terms of a common expression pattern of the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell surface-associated HSPGs have been described as tumor biomarkers being differentially regulated during tumorigenesis [3, 24, 25]. Recently, a direct relationship between growth factor-mediated signaling, ERs and ECM components has been shown.…”
Section: Extracellular Matrices In Breast Cancer: Focus On the Promentioning
confidence: 99%
“…Notably, this study also showed that glypican-1 stimulates the mitogenic response of two breast cancer cell lines to -heparin binding epidermal growth factor (HB-EGF) and to FGF2, suggesting that the up-regulation of glypican-1 could play a role in breast cancer progression. It should be noted, however, that a more recent study of 23 breast tumor samples by qRT-PCR could not detect significant over-expression of glypican-1 [24]. …”
Section: The Role Of Glypicans In Breast Cancer Progressionmentioning
confidence: 99%